Temporal variability patterns in solar radiation estimations. (June 2016) - Vindel, José M.; Navarro, Ana A.; Valenzuela, Rita X.; Zarzalejo, Luis F.
Abstract: In this work, solar radiation estimations obtained from a satellite and a numerical weather prediction model in mainland Spain have been compared. Similar comparisons have been formerly carried out, but in this case, the methodology used is different: the temporal variability of both sources of estimation has been compared with the annual evolution of the radiation associated to the different study climate zones. The methodology is based on obtaining behavior patterns, using a Principal Component Analysis, following the annual evolution of solar radiation estimations. Indeed, the adjustment degree to these patterns in each point (assessed from maps of correlation) may be associated with the annual radiation variation (assessed from the interquartile range), which is associated, in turn, to different climate zones. In addition, the goodness of each estimation source has been assessed comparing it with data obtained from the radiation measurements in ground by pyranometers. For the study, radiation data from Satellite Application Facilities and data corresponding to the reanalysis carried out by the European Centre for Medium-Range Weather Forecasts have been used. Highlights: Annual variability patterns have been found in Spain for both satellite and numerical model estimations. In the case of the satellite, the pattern is especially followed in zones with an accused annual variation. In the case of the numerical model, the pattern is followed with a very high correlation along the whole country. The satellite can distinguish better the different climate zones that are present in the territory.